A case of ascending paralysis in pregnancy: Thiamine deficiency mimicking Guillain–Barré syndrome - De Yee Gan; Chin Meng Lee; Shakirin Pairan; Raja Ahmad Reza Raja Lope Ahmad; Hamdi Najman Achok (Clinical Medicine)
Thiamine (vitamin B1) deficiency may present with diverse symptoms and is often triggered by chronic alcoholism, severe malnutrition or hyperemesis gravidarum. While typically diagnosed clinically, atypical presentations may delay recognition and treatment.We report a 26-year-old pregnant woman in her second trimester with prolonged nausea and vomiting since early pregnancy. She developed ascending lower limb paralysis, dysarthria, horizontal nystagmus, and lagophthalmos. Initially managed as hypokalaemia periodic paralysis with thyrotoxicosis and later Guillain–Barré syndrome (GBS), her symptoms worsened despite treatment.Subsequent MRI brain imaging revealed findings indicative of Wernicke encephalopathy, prompting high-dose thiamine therapy. This resulted in significant neurological improvement.This case underscores the importance of considering thiamine deficiency in atypical neurological presentations, particularly in pregnancy. Early recognition and prompt treatment can mitigate irreversible neurological damage, emphasising the necessity of maintaining a high index of suspicion in clinical practice.